Strengthening forages and pasture seed systems for climate-resilient, productive and inclusive mixed farming in Malawi: A case for establishing a forages Technical Working Group (TWG) - Homann-kee Tui, Sabine; Hami, Joseph; Makalani, Andrew; Banda, Mcloyd; Gausi, Harriet; Kayinga, Walusako; Chikagwa-Malunga, Susan; Kulemeka, Elestina; Mwendia, Solomon; Notenbaert, An (2025)
Livestock is central to the livelihoods of most rural households in Malawi, significantly contributing to nutrition, income, soil fertility and resilience. Although livestock numbers are increasing, productivity (production per animal) remains below potential. One of the major binding constraints in the livestock sector is insufficient quantity and quality of livestock feed throughout much of the year. These feed gaps are driven by shrinking grazing areas due to increased conversion of grazing land to cropland, land fragmentation and land degradation from continuous cultivation leading to declining soil fertility and increased erosion. Other contributing factors are the weak and underdeveloped pasture seed systems, inadequate pasture management, and low farmer awareness leading to limited adoption of cultivated forages. Smallholder farmers typically own a few animals; it is therefore important that these animals are productive and well-integrated into the mixed farming system. The currently fragmented institutional landscape and absence of coordinated leadership hinder the necessary integrated approach. A Forages Technical Working Group (TWG) is proposed as a national coordination and advisory platform to align stakeholders, strengthen pasture seed systems, and scale forage–livestock–crop integration for improved livestock production, whilst also enhancing land restoration and climate-resilience.